Exploratory Assessment of Factors that Influence Quality of Local Irrigation Water Governance in Uzbekistan - Swinkels, Rob; Romanova, Ekaterina; Kochkin, Evgeny (World Bank, Washington, DC, 2016)
Agriculture in Uzbekistan is almost entirely dependent on irrigation. However, despite reforms to institutional arrangements, much of Uzbekistan’s irrigation is reportedly caught in a vicious cycle of inadequate operation and maintenance, low cost recovery, and agricultural productivity that is often moderate or low; in addition, many farmers earn low incomes (World Bank, 2013).Few incentives exist to save water because farmers do not see the direct cost of water provision.This study was undertaken with the aim of contributing to better irrigation water management in Central Asia, beginning in Uzbekistan. It identifies factors and conditions that positively affect the performance of local irrigation water management institutions. The analytical framework for this assessment is formed by the eight design principles for the management of common-pool resources developed by Ostrom (1990). These design principles are in essence factors that are associated with successful collective action in governing common-pool resources such as irrigation water, forests, and fishing areas. By determining why these principles are met in some cases and not in others, and what factors are behind this variation, the author can identify measures that promote these factors/conditions in irrigation schemes. This study was undertaken with the aim of contributing to better irrigation water management in Central Asia, beginning in Uzbekistan. It identifies factors and conditions that positively affect the performance of local irrigation water–management institutions. The study also prepared an associated diagnostic tool that will help design measures and program interventions to strengthen these institutions in ongoing or future irrigation operations. Lastly, the work intends to contribute to an exchange of good practices and knowledge sharing among relevant stakeholders across the Central Asia region.